2018
DOI: 10.1590/s1679-45082018rc4025
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunohistochemical study of melanotic neuroectodermal tumor of infancy in the maxilla

Abstract: Melanotic neuroectodermal tumor of infancy is a rare and fast-growing neoplasm. In this study, we describe the case of a 6-month-old female patient, who presented swelling in the anterior maxilla. Tomographic reconstruction showed an unilocular hypodense and expansive area associated with the upper right central primary incisor. The presumptive diagnoses were dentigerous cyst, adenomatoid odontogenic tumor, melanotic neuroectodermal tumor of infancy and rhabdomyosarcoma, and an incisional biopsy was performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…More than 500 cases of MNTI have been reported worldwide by Rachidi et al In addition to the 472 cases reported between 1918 and 2013 as a part of the largest retrospective study, [5] we found 49 cases reported between January 2014 and June 2021 by searching PubMed [3,4,9–32,36–38] . In a systematic review of 472 MNTI cases, [5] most cases developed within 1 year of age, with more than 90% of cases occurring in the craniofacial region, such as the maxilla (60.3%), skull (18.1%), and mandible (10.3%).…”
Section: Discussionmentioning
confidence: 75%
“…More than 500 cases of MNTI have been reported worldwide by Rachidi et al In addition to the 472 cases reported between 1918 and 2013 as a part of the largest retrospective study, [5] we found 49 cases reported between January 2014 and June 2021 by searching PubMed [3,4,9–32,36–38] . In a systematic review of 472 MNTI cases, [5] most cases developed within 1 year of age, with more than 90% of cases occurring in the craniofacial region, such as the maxilla (60.3%), skull (18.1%), and mandible (10.3%).…”
Section: Discussionmentioning
confidence: 75%
“…However, all those synonyms are obsolete and not recommended. The name of MNTI is widely accepted now and the tumor is proposed to be of neural crest origin because the tumor produces VMA ( 2 ) and has heterogeneous cellular phenotype microscopically which explains by the mesodermal and ectodermal morphological features displayed by neural crest cells at different stages of their ontogeny ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…MNTI is categorized as one type of benign maxillofacial bone and cartilage tumors in 4 th edition of WHO Classification of Head and Neck Tumors. However, radiologically, MNTI always presented with well circumscribed hypodense mass, but may show excessive bone destruction and displacement of dental follicles under CT scan ( 13 ). The present case showed a well-defined, unilocular, osteolytic lesion causing expansion and destruction of the maxillary cortical bone, which was in line with the previous publications.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is also used, especially for patients who cannot tolerate chemotherapy. Some pPNET patients undergo surgery after chemotherapy or radiotherapy but cannot receive adjuvant chemotherapy and radiotherapy given that combined therapy will increase the risk of complications [ 7 ].…”
Section: Discussionmentioning
confidence: 99%